Working from home: Heterogeneous effects on hours worked and wages - Melanie Arntz; Sarra Ben Yahmed; Francesco Berlingieri (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Working from home (WfH) has become much more common since the early 2000s. We exploit the German Socio-Economic Panel between 1997 and 2014 to investigate how such a work arrangement affects labour market outcomes and life satisfaction. We find that childless employees work an extra hour per week of unpaid overtime and report higher satisfaction after taking up WfH. Among parents, WfH reduces the gender gap in working hours and monthly earnings, as contractual hours increase more among mothers. Hourly wages, however, increase with WfH take-up among fathers, but not among mothers unless they change employer. This points to poorer bargaining outcomes for women compared to men when staying with the same employer. Controlling for selection into paid employment due to changes in unobserved characteristics or preferences does not affect the magnitude of the effects.
Keywords: J2; J31; O33; 330; working from home; working hours; wages; gender; flexible work arrangements.